2019
DOI: 10.1002/cbic.201800787
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of Protein‐Specific Methylation in Mammalian Cells

Abstract: Abundant post‐translational modification through methylation alters the function, stability, and/or localization of a protein. Malfunctions in post‐translational modification are associated with severe diseases. To unravel protein methylation sites and their biological functions, chemical methylation reporters have been developed. However, until now, their usage was limited to cell lysates. Herein, we present the first generally applicable approach for imaging methylation of individual proteins in human cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…18 Very recently, Zumbusch et al took advantage of ProSeAM 8 to introduce an alkyne group into a biomolecule, followed by Cu-catalyzed cycloaddition employing fluorescent azide probes for direct imaging of individual proteins in human cells. 19 For synthetic purposes, however, the expressive activity of SeAM analogs, their relatively easy decomposition, and timeconsuming and expensive preparation hampered their appli-…”
Section: Selenonium and Telluronium Salts As Sources Of Electrophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Very recently, Zumbusch et al took advantage of ProSeAM 8 to introduce an alkyne group into a biomolecule, followed by Cu-catalyzed cycloaddition employing fluorescent azide probes for direct imaging of individual proteins in human cells. 19 For synthetic purposes, however, the expressive activity of SeAM analogs, their relatively easy decomposition, and timeconsuming and expensive preparation hampered their appli-…”
Section: Selenonium and Telluronium Salts As Sources Of Electrophilesmentioning
confidence: 99%
“…Nevertheless, the best results were obtained when the framework of the chalcogenium salt was embedded with strong electron-withdrawing groups, such as the 3,7-dinitro derivatives 23d and 23e. A remarkable correlation between the trifluoromethylation power of chalcogenonium salts 23a-g and 25 and a decrease in the electron density of the CF 3 group on these compounds could be defined based on the 19 F NMR chemical shifts of the trifluoromethyl groups. Mechanistically, it was demonstrated that different reaction pathways might be invoked to describe the trifluoromethylation of substrates with salts 23a-g or 25.…”
Section: Reviewmentioning
confidence: 99%
“…Some metabolite analogs such as ProSeAM and the NAD + analog are not membrane-permeable and must be loaded invasively via liposomes or electroporation. 80,81 Efforts to engineer biosynthetic pathways to create cell-impermeant metabolite analogs intracellularly from cell-permeant precursors are promising, 97,98 although these have not yet been applied to proteoform detection.…”
Section: Limitations Of Metabolic Labelingmentioning
confidence: 99%
“…3c ) and subsequent cy3–azide conjugation. 80 SAM-based labeling has been applied to study the subcellular localization of Foxo1 which is affected by its methylation state, via FLIM-FRET. Poly(ADP-ribos)ylation of ARTD protein was also reported using EGFP fusion and a fluorophore conjugated NAD + analog ( Fig.…”
Section: Molecular Tools To Detect Proteoforms Involving Addition Of ...mentioning
confidence: 99%
“…4a). Moreover, Doll et al presented the first generally applicable method to detect histone methylation in HEK293T and HeLa cells based on the combination of a biochemical reporter and ligation reactions, and use fluorescence lifetime imaging microscopy to capture resonance energy transfer (Doll et al 2019). Using this approach, they succeeded in imaging the methylation of histone 4 in these two human cell lines, along with the detection of the kinase Akt1, the tumor suppressor p53, and the transcription factor Foxo1, all of which significantly participate in carcinogenesis.…”
Section: Histone Methylationmentioning
confidence: 99%